A greyhound of a girl - Roddy Doyle (Marion Lloyd, 2012)
12-year-old Mary's beloved grandmother is near the end of her life. Letting go is hard - until Granny's long-dead mammy appears at Mary's door, returning to help her dying daughter say goodbye. But first she needs someone to drive them all on a visit to the past.